2005
DOI: 10.1128/aac.49.5.1808-1812.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Safety and Pharmacokinetic Study of Chimeric Murine-Human Monoclonal Antibody cαStx2 Administered Intravenously to Healthy Adult Volunteers

Abstract: Hemolytic-uremic syndrome (HUS) is a serious complication of infection by Shiga toxin-producing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 10 publications
1
51
1
Order By: Relevance
“…Headache was the most common event reported. The development of human anti-mAb antibodies was reported as undetected for tefibazumab, 19 but 4 of 17 subjects (24%) dosed with caStx2 developed HACA, 18 though like the anti-chmAb7F9 reported here, the response was not dose related.…”
Section: Similar Mab Doses Have Been Used Previously In Human Studiesmentioning
confidence: 72%
See 2 more Smart Citations
“…Headache was the most common event reported. The development of human anti-mAb antibodies was reported as undetected for tefibazumab, 19 but 4 of 17 subjects (24%) dosed with caStx2 developed HACA, 18 though like the anti-chmAb7F9 reported here, the response was not dose related.…”
Section: Similar Mab Doses Have Been Used Previously In Human Studiesmentioning
confidence: 72%
“…17,19 Pagibaximab is somewhat longer at 33 days 20 and caStx2 is shorter at 8.6 d 18 The long ch-mAb7F9 elimination half-life could be a substantial improvement over many small molecule medications used to treat METH users. Because of its 18-day half-life, ch-mAb7F9 dosing should be no more frequent than every 3 weeks, which will increase compliance for motivated patients.…”
Section: Similar Mab Doses Have Been Used Previously In Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we observed that the OIA method was more sensitive than the EIA (14). In addition, therapies such as humanized monoclonal antibodies that can be passively administered to protect against Shiga toxins are in development (5,13). Once these therapies are available, at-risk patients who have been identified by rapid toxin detection methods can be treated promptly, since the efficacy of such interventions is likely to be proportional to the speed with which therapy is administered.…”
Section: Discussionmentioning
confidence: 96%
“…72 Many therapeutic Abs demonstrate rapid clearance when their serum concentrations fall below a threshold concentration, corresponding to the point of equal amounts of Ab and target. [73][74][75] Volumes of distribution After intravenous administration, mAbs initially distribute into a volume roughly equal to the plasma volume (0.045 L/kg) 3,73,76 and on approaching steady state the volume of distribution increases to approximately 0.1 L/kg, reflecting only limited extravascular distribution. [77][78][79] Biodistribution studies in animals lacking the target Ag have shown that the largest percentage of the dose of mAb is in the plasma and that whole-body distribution predominantly targets organs that are highly perfused with blood.…”
Section: Pharmacokinetic Considerations Systemic Clearancementioning
confidence: 99%